THE ANALYSIS OF SOCIO-ECONOMIC CONDITIONS FOR ORGANIC PRODUCTION IN MONTENEGRO - Jovanović, Miomir; Despotović, Aleksandra (Economics of Agriculture, 2012)
Food production and agriculture still play an important role in the economic development of Montenegro. The share of agriculture in total GDP of Montenegro was 8.4 % (2008) and share of Gross Value Added in total GDP was 6.9% (2007). One of the structural characteristics of Montenegrin food production is higher share of agriculture in gross domestic product in comparison to the food processing sector. This indicates a low level in finalization of agricultural products, as well as the emphasized sales of agro-food products through unregistered trade channels. The prevailing existence of extensive agriculture in Montenegro provides a good basis for development of organic agriculture. Development of the organic sector is therefore considered as an important and contributing factor for the overall economic development and rural poverty alleviation. The paper analyzes the socio economic situation of agricultural producers in Montenegro in terms of procedures for organic production.